Analisis Kepuasan Pengguna Aplikasi PeduliLindungi Masyarakat Kota Batam Menggunakan Metode End-User Computing Satisfaction (EUCS) - Prasetyaningsih, Sandi; Jati, Mustika Embun (JURNAL INTEGRASI, 2024)
Since the emergence of Covid-19 in Indonesia, one of the efforts made to break the chain of transmission is the PeduliLindungi application developed by the Ministry of Communication and Informatics to track people suspected of being exposed to Covid-19. Many factors are needed to recognize that an application is good quality. One very important factor is user satisfaction, so research is needed on measuring the level of user satisfaction with the PeduliLindungi application. By using the EUCS (End-User Computing Satisfaction) method which involves the general public of Batam City who have carried out the Covid-19 vaccination as respondents, this study aims to determine the level of user satisfaction and how much influence the EUCS variables have on the level of satisfaction for PeduliLindungi application users. The results showed that the content, accuracy, format, ease of use, timeliness and user statisfaction variable as a whole were valid and reliable with an effect of 36.4% on user satisfaction. Of the 5 hypotheses, only the timeliness variable has a significant effect on user satisfaction.